Moving to greater exchange rate flexibility operational aspects based on lessons from detailed country experiences - Ötker-Robe, Inci...[et al.] (IMF WashingtonUS, 2007)
Presents the concrete steps a selected number of countries took in transitioning to greater exchange rate flexibility. Elaborates on the operational attributes that proved helpful in promoting successful transitions.